The outcome competency framework for practitioners in infection prevention and control: use of the outcome logic model for evaluation. Issue 1 (January 2014) - Burnett, E; Curran, E; Loveday, HP; Kiernan, MA; Tannahill, M
Healthcare is delivered in a dynamic environment with frequent changes in populations, methods, equipment and settings. Infection prevention and control practitioners (IPCPs) must ensure that they are competent in addressing the challenges they face and are equipped to develop infection prevention and control (IPC) services in line with a changing world of healthcare provision. A multifaceted Framework was developed to assist IPCPs to enhance competence at an individual, team and organisational level to enable quality performance and improved quality of care. However, if these aspirations are to be met, it is vital that competency frameworks are fit for purpose or they risk being ignored. The aim of this unique study was to evaluate short and medium term outcomes as set out in the Outcome Logic Model to assist with the evaluation of the impact and success of the Framework. This study found that while the Framework is being used effectively in some areas, it is not being used as much or in the ways that were anticipated. The findings will enable future work on revision, communication and dissemination, and will provide intelligence to those initiating education and training in the utilisation of the competences.